Diseño eléctrico Villas de Elizabeth (2022)
This degree work is directed to the calculations and design of the construction project of the closed complex Villas de Elizabeth project with which it is sought to receive profits for the investment made; the pertinent electrical calculations will be made based on the norms and technical regulations according to construction of electrical infrastructure